Phenoloxidase activation in the embryo of the common cuttlefish Sepia officinalis and responses to the Ag and Cu exposure (2009)
The prophenoloxidase (proPO) system catalyzing the melanin production is considered as implicated in the innate immune system in invertebrates. The phenoloxidase (PO)-like activity was detected in the cuttlefish embryo sampled at the end of the organogenesis and few hours before hatching. Various modulators of the PO activity were used to assess the triggering of the proPO activating system. The results demonstrated the evidence of a true PO activity in the cuttlefish embryo. However, SDS and LPS granted contrasting effects on the PO-like activity between the developmental stages suggesting a progressive maturation of the proPO system from the embryonic to the juvenile stages. In eggs exposed to dissolved trace metals all along the embryonic development, Ag (1.2 mg L1 ) inhibited the PO-like activity in the cuttlefish embryo except at hatching time, suggesting the synthesis of a new ‘‘juvenile’’ form of the PO enzyme. In similar conditions as for Ag, Cu (230 mg L1 ) stimulated and then inhibited the PO-like activity according to a progressive metal accumulation within the egg and suggesting the occurrence of a threshold, above which the toxicity of the essential metal reduced the PO activity.